Heavy metal levels and sources in suspended particulate matters of the glacier watersheds in Northeast Tibetan Plateau - Wu, Rui; Dong, Zhiwen; Cheng, Xiping; Brahney, Janice; Jiao, Xiaoyu; Wu, Lihua (Frontiers in Environmental Science, 2022)
This study collected summer meltwater runoff samples from several glacier watershed of the northeast Tibetan Plateau during June-July 2017, and measured the concentrations of 17 trace elements in suspended particulate matter (SPM), in order to reveal the spatial distribution and water quality in remote glacier watershed. Results showed that, concentration of heavy metal elements showed large spatial differences, with relatively high in Yuzhufeng Glacier basin, ranging from 0.57 µg/L (In) to 1551.6 µg/L (Ba); whereas it was the lowest in Qiyi Glacier basin, ranging from 0.02 to 85.05 µg/L. Moreover, enrichment factors (EFs) showed significantly higher value in the downstream than that of upper glacier region of the watershed. Some heavy metals with low EFs (e.g. Li, Be, Co, Ga, Rb, Mo, Ba) mainly originated from crust dust, while others with high EFs (e.g. Cr, Ni, Cd, Sb, Cs) probably originated from anthropogenic pollution sources. Spatially, the EFs of heavy metals were higher in Yuzhufeng and Laohugou Glacier basins; while in other regions EFs were relatively low, which may be caused by regional land surface and atmospheric environmental difference surrounding the various glacier watersheds. Compared with other remote locations in global range, heavy metals level (e.g. Cu, Ni, and Zn) in this region is relatively higher and water quality of the glacier watersheds was relatively clean, with low EFs though affected by regional anthropogenic activities. Heavy metal pollutants mainly originated from atmospheric transport and inputs from surrounding anthropogenic emissions, such as non-ferrous metal smelting, mining, transportation emissions and fossil fuel combustion. Backward trajectory and AOD analysis demonstrated the potential air pollutants transport to the glacier snowpack from the surrounding cities and suburbs, and melted out and released into meltwater runoff. Therefore, this study provides a new perspective and understanding of the cryosphere water environment evaluation in the Tibetan Plateau region.